2014
DOI: 10.1155/2014/276323
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of Graphene Oxide: Cement Nanocomposites

Abstract: We investigate the performance of graphene oxide (GO) in improving mechanical properties of cement composites. A polycarboxylate superplasticizer was used to improve the dispersion of GO flakes in the cement. The mechanical strength of graphene-cement nanocomposites containing 0.1–2 wt% GO and 0.5 wt% superplasticizer was measured and compared with that of cement prepared without GO. We found that the tensile strength of the cement mortar increased with GO content, reaching 1.5%, a 48% increase in tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(116 citation statements)
references
References 29 publications
3
89
0
12
Order By: Relevance
“…This technology is owned by Monash University and is protected by Patent PCT/AU2012/001582. Babak, Abolfaz, Alimorad, and Parviz (2014) synthesised GO using exfoliation of graphite oxide prepared by a colloidal suspension route. They used it to fabricate GO-cement nanocomposites by means of an ultrasonic method and concluded that the use of an optimal percentage (1.5 wt%) of GO nanoplatelets caused a 48% increase in the tensile strength of the cement mortar specimens.…”
Section: Graphene Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…This technology is owned by Monash University and is protected by Patent PCT/AU2012/001582. Babak, Abolfaz, Alimorad, and Parviz (2014) synthesised GO using exfoliation of graphite oxide prepared by a colloidal suspension route. They used it to fabricate GO-cement nanocomposites by means of an ultrasonic method and concluded that the use of an optimal percentage (1.5 wt%) of GO nanoplatelets caused a 48% increase in the tensile strength of the cement mortar specimens.…”
Section: Graphene Oxidementioning
confidence: 99%
“…Using FE-SEM observation of the fracture surface of the samples containing 1.5 wt% GO, these authors revealed that the GO nanoplatelets were well dispersed and no GO agglomerates were seen in the matrix. Babak et al (2014) showed the growth of C-S-H gels in GO cement mortar because of the nucleation of C-S-H by the GO flakes. Due to the higher surface energy and the presence of hydrophilic groups on the GO surfaces, the hydrated cement products deposited on the GO flakes acted as a nucleation site.…”
Section: Graphene Oxidementioning
confidence: 99%
“…Those impressive mechanical natures stimulated interesting research in applying graphene as a superlative filler in reinforced composites [24,25]. Graphene oxide (GO), which possesses a high specific surface area and ultrahigh strength [26], can easily form composites with polymer and ceramic materials with chemical bonds, affecting cement hydration crystal shape and increasing its flexural and compressive strength [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However it is possible to present some that may lead to further developments. For example, Babak et al [55] synthesized GO using exfoliation of graphite oxide prepared by a colloidal suspension route of polycarboxylate superplasticizer. They used it to fabricate GO-cement nanocomposites by means of an ultrasonic method and concluded that the use of an optimal percentage (1.5 wt%) of GO nanoplatelets caused a 48% increase in the tensile strength of the cement mortar specimens.…”
Section: Graphene Oxidementioning
confidence: 99%